Differences in peripheral and central metabolites and gut microbiome of laying hens with different feather-pecking phenotypes - Wang, Chao; Li, Yaling; Wang, Haoliang; Li, Miao; Rong, Jinsheng; Liao, Xindi; Wu, Yinbao; Wang, Yan (Frontiers in Microbiology, 2023)
Background: Feather pecking (FP) is a maladaptive behavior in laying hens that is associated with numerous physiological traits, including those involving the central neurotransmitter system and the immune system, which have been identified in many species as being regulated by the gut microbiota via the “microbiota-gut-brain” (MGB) axis. Yet, it is unknown whether and how gut microbiota influences FP by regulating multiple central neurotransmission systems and immune system. Methods: This study was measured the prevalence of severe FP (SFP) in the commercial layer farm. The chicken flock with the highest frequency of SFP were selected for FP phenotype identification. Nontargeted metabolomics was performed to investigated the differences in the peripheral and central metabolites and 16S rDNA sequencing was performed to investigated the differences in gut microbiome of laying hens with different FP phenotypes. Correlation analysis was performed to determine the potential mechanism by which the disturbed gut microbiota may modulate host physiology and behavior. Results: The results showed that pullets (12 weeks of age) showed significantly higher SFP frequencies than chicks (6 weeks of age) and adults (22 weeks of age) (P < 0.05). Compared to neutrals (N), peckers (P) exhibited the stress-induced immunosuppression with the increased plasma levels of corticosterone and norepinephrine, and the decreased plasma levels of IgA, IL-1, IL-6 and tumor necrosis factor α (P < 0.05). In the cecum, the relative abundances of Bacteroides and Gemmiger were higher in the P group, while Roseburia, Ruminococcus2, Anaerostipes, Lachnospiracea_incertae_sedis and Methanobrevibacter were more enriched in the N group. Moreover, increased plasma levels of L-tryptophan, beta-tyrosine and L-histidine were found in the P group (P < 0.05). Notably, in the P group, hippocampal levels of L-tryptophan, xanthurenic acid, L-histidine and histamine were improved and showed a positive association with L-glutamic acid levels. Plasma levels of L-tryptophan, beta-tyrosine and L-histidine were both positively correlated with Bacteroides abundance but negatively correlated with Methanobrevibacter abundance. Conclusion: Overall, these findings suggest that the development of FP may be affected by the gut microbiota, which regulates the central glutamatergic nerve system by altering the metabolism of tryptophan, histidine and tyrosine.